Construction of functional tissue-engineered microvasculatures using circulating fibrocytes as mural cells - Xiaolin Wang; Hong Tan; Harsha P Gunawardena; Jin Cao; Lu Dang; Hongbing Deng; Xueyong Li; Hongjun Wang; Jinqing Li; Caibin Cui; David A Gerber (Journal of Tissue Engineering)
Mural cells are essential for maintaining the proper functions of microvasculatures. However, a key challenge of microvascular tissue engineering is identifying a cellular source for mural cells. We showed that in vitro , circulating fibrocytes (CFs) can (1) shear and stabilize the microvasculatures formed by vascular endothelial cells (VECs) in a collagen gel, (2) form gap junctions with VECs and (3) induce basement membrane formation. CFs transplanted into nude mice along with VECs in either collagen gel or Matrigel exhibited activities similar to those mentioned above, that is, sheathing microvasculatures formed by VECs, inducing basement membrane formation and facilitating the connection of the engineered microvasculatures with the host circulation. Interestingly, the behaviour of CFs also differs from that of human brain vascular pericytes (HBVPs) in vitro , which often infiltrate the lumen of capillary-like structures in a mosaic pattern, actively proliferate and exhibit lower endocytosis and migration capacities. We concluded that CFs are a suitable cellular source for mural cells in the construction of tissue-engineered microvasculatures.